Developmental timing of a sensory-mediated larval surfacing behavior correlates with cessation of feeding and determination of final adult size. - Wegman, L.J.; Ainsley, J.A.; Johnson, W.A. (Developmental Biology, 2010)
Controlled organismal growth to an appropriate adult size requires a regulated balance between nutrient resources, feeding behavior and growth rate. Defects can result in decreased survival and/or reproductive capability. Since Drosophila adults do not grow larger after eclosion, timing of feeding cessation during the third and final larval instar is critical to final size. We demonstrate that larval food exit is preceded by a period of increased larval surfacing behavior termed the Intermediate Surfacing Transition (IST) that correlates with the end of larval feeding. This behavioral transition occurred during the larval Terminal Growth Period (TGP), a period of constant feeding and exponential growth of the animal. IST behavior was dependent upon function of a subset of peripheral sensory neurons expressing the Degenerin/Epithelial sodium channel (DEG/ENaC) subunit, Pickpocket1(PPK1). PPK1 neuron inactivation or loss of PPK1 function caused an absence of IST behavior. Transgenic PPK1 neuron hyperactivation caused premature IST behavior with no significant change in timing of larval food exit resulting in decreased final adult size. These results suggest a peripheral sensory mechanism functioning to alter the relationship between the animal and its environment thereby contributing to the length of the larval TGP and determination of final adult size.